Co-Ability and embodied data: blurring the lines between human and nonhuman entities in an interconnected world - Dezso, Renata (Frontiers in Human Dynamics, 2024)
This paper explores the dynamic interplay between human and nonhuman entities, focusing on how embodied data representation is distributed. It examines how predictive coding, which utilizes preconceived knowledge, interacts with tangible experiences to shape our understanding of the world. Emphasizing I propose the concept of co-Ability as a deep underlying explanatory framework for understanding adaptive behaviors within a networked world. A non-verbal dialogue between humans and a data-saturated environment is analyzed through an action-oriented perspective and the predictive coding framework in cognition, utilizing digital craft and rapid prototyping.. This transformative approach augments human interaction with digital landscapes through tangible prototypes, bridging physical experience with abstract information and identifying potential ways to conceptualize data in a material way. The article discusses the various aspects of connectivity among network agents and the evolving nature of these connections as they adapt to real-world conditions and dynamic shifts in data, highlighting that information exchange in an interconnected network is more than bilateral; it generates ripple effects that extend beyond immediate connections. These reciprocal exchanges simultaneously alter both digital and analog domains, with data constantly bifurcating into multiple pathways and outcomes.A significant challenge addressed in this paper is the question of how to frame information in a material way, inviting further exploration.